Tunnelling in the urban environment : Geotechnique Symposium in Print 2017 - Zdravkovic, Lidija (ICE Publishing, 2018)
With urban tunnel construction growing worldwide, the ability to accurately predict the ground and structural response to tunnelling and the associated risks is now more important than ever before. Engineers are expected to consider all aspects of tunnel engineering in order to safeguard existing infrastructure, by employing field monitoring, physical modelling and numerical analysis in developing a detailed knowledge of multiple soil structure interactions. The Geotechnique Symposium in Print took place at the Institution of Civil Engineers on 14th September 2017 to discuss the wider aspects of tunnelling in urban locales. The papers included here bring together important international research presented at the symposium.